Icacos Beach - (:unkn) unknown (My University, 2009)
Located on the south western most point of Trinidad, Icacos is only eleven kilometers (11km) from mainland Venezuela. The village was named by original Amerindian inhabitants after a common shrub of the rose family, Icaco.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Icacos; Fishing villages--Trinidad and Tobago; Beaches--Trinidad and Tobago; Coconut palm--Trinidad and Tobago